2005
DOI: 10.1038/sj.onc.1209116
|View full text |Cite
|
Sign up to set email alerts
|

Selective destruction of glioblastoma cells by interference with the activity or expression of ATF5

Abstract: Glioblastoma multifome is the most common and most aggressive primary brain tumor with no current curative therapy. We found expression of the bZip transcription factor ATF5 in all 29 human glioblastomas and eight human and rat glioma cell lines assessed. ATF5 is not detectably expressed by mature brain neurons and astrocytes, but is expressed by reactive astrocytes. Interference with ATF5 function or expression in all glioma cell lines tested causes marked apoptotic cell death. In contrast, such manipulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
160
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(169 citation statements)
references
References 30 publications
8
160
1
Order By: Relevance
“…Recently, ATF5 was found to be expressed in all series of 29 human glioblastomas (GBMs), in addition to and all 7 human and rodent GBM cell lines surveyed. 4 Another group also confirmed the presence of ATF5 in GBM and the levels of expression appeared to correlate with patient survival.8 ATF5 was also shown to be upregulated in follicular carcinomas of the thyroid. 7 In addition, it has been shown that a variety of genes, including ATF5, involved with cell proliferation and inhibition of apoptosis, are downregulated upon treatment of prostate cancer cells with phytochemicals (indole-3-carbinol) 9 and chemotherapeutic agents (docetaxel and estramustine).…”
mentioning
confidence: 51%
“…Recently, ATF5 was found to be expressed in all series of 29 human glioblastomas (GBMs), in addition to and all 7 human and rodent GBM cell lines surveyed. 4 Another group also confirmed the presence of ATF5 in GBM and the levels of expression appeared to correlate with patient survival.8 ATF5 was also shown to be upregulated in follicular carcinomas of the thyroid. 7 In addition, it has been shown that a variety of genes, including ATF5, involved with cell proliferation and inhibition of apoptosis, are downregulated upon treatment of prostate cancer cells with phytochemicals (indole-3-carbinol) 9 and chemotherapeutic agents (docetaxel and estramustine).…”
mentioning
confidence: 51%
“…ATF5 is widely detected upon immunohistochemical staining of carcinoma tissue microarrays, and nuclear localization of ATF5 is higher in neoplastic tissues than in non-neoplastic tissues [3]. Recent studies have shown that ATF5 plays an important role in promoting cell survival in a variety of cell types, including breast cancer, glioblastoma, cervical cancer, lymphocytes, and cardiomyocytes [3,4,5,6], while several other studies reported that ATF5 is not required for cell survival in lung cancer, neuro progenitors, adrenal glands, embryonic kidney cells, astrocytes, oligodendrocyte precursors, mouse embryonic stem cells, or non-neoplastic breast cells [3,7,8,9,10,11]. Although the role of ATF5 as a survival-related protein has been extensively reported, few studies have been performed 5 to reveal the relationship between ATF5 expression and cancer cell invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…ATF5 has been found to be overexpressed in human glioblastomas and human and rat glioma cell lines (16,23,24). Interference of ATF5 expression in glioma cells leads to apoptotic cell death both in vitro and in vivo (16). Additionally, ATF5 overexpression in breast carcinoma cells has been detected (15,22), and interference of ATF5 expression selectively triggers their death.…”
Section: Introductionmentioning
confidence: 99%
“…It may be a potent repressor of p53 and its elevated expression may be related to enhanced malignant phenotypes (21). ATF5 has been found to be overexpressed in human glioblastomas and human and rat glioma cell lines (16,23,24). Interference of ATF5 expression in glioma cells leads to apoptotic cell death both in vitro and in vivo (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation